2009
DOI: 10.1080/16506070903121042
|View full text |Cite
|
Sign up to set email alerts
|

Can Asylum-Seekers with Posttraumatic Stress Disorder Be Successfully Treated? A Randomized Controlled Pilot Study

Abstract: Rates of posttraumatic stress disorder (PTSD) are exceptionally high among asylum-seekers. Reportedly, stressors caused by the asylum procedure and psychological consequences of torture contribute to the maintenance of symptoms and interfere with treatment. In a pilot randomized controlled trial, the authors examined the efficacy of trauma-focused treatment in 32 asylum-seekers with PTSD resulting from state-sponsored violence and other traumatic events. Narrative exposure therapy (NET) was compared with treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
131
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 31 publications
5
131
0
6
Order By: Relevance
“…It is well-known that specialized treatment centres often admit treatment-resistant refugees with higher symptom severity (Drozdek, 2015). In fact, the mean scale score of the investigated sample is comparable to those of other intervention studies on traumatized refugees in specialized treatment centres in terms of symptoms of depression, anxiety and PTSD (Carlsson et al, 2010; Neuner et al, 2010; Schock, Bottche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016). Thus, the results of the current study should be interpreted against this background.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is well-known that specialized treatment centres often admit treatment-resistant refugees with higher symptom severity (Drozdek, 2015). In fact, the mean scale score of the investigated sample is comparable to those of other intervention studies on traumatized refugees in specialized treatment centres in terms of symptoms of depression, anxiety and PTSD (Carlsson et al, 2010; Neuner et al, 2010; Schock, Bottche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016). Thus, the results of the current study should be interpreted against this background.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, high symptom loads after treatment were found in different studies including traumatized refugees (e.g. Buhmann et al, 2015; Carlsson et al, 2010; Neuner et al, 2010), suggesting that even after successful treatment, many patients still meet diagnostic criteria for trauma-related disorders and might still need low-threshold treatment options after therapy. To meet this need and to prevent strong and/or long-lasting symptom relapses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to trauma-focused treatments, such as Narrative Exposure Therapy (Neuner et al, 2010), and in line with the transdiagnostic concept of the treatment, improvement in the total score of the GHQ-28 was much larger than in the PLC-5, suggesting that the primary effect of the treatment may have been stronger on general mental health than on specific symptoms of PTSD. The reduction of the PCL-5 was lower than the controlled effects of RCTs with trauma-focused treatments in a recent meta-analysis, among them Narrative Exposure Therapy as the best-evaluated (Nosè et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Systematic review of treatment modalities for PTSD in refugee populations found that no treatment modality was firmly supported, but there was evidence for the effectiveness of narrative exposure therapy and cognitive-behavioral therapy (e.g., Crumlish, & O'Rourke, 2010, Robjant, & Fazel, 2010Neuner et al, 2009). There is an empirical evidence of the effectiveness of trauma-focused CBT on refugees (e.g., Kruse, Joksimovic, Cavka, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%